Paintability - Innes, Jocasta; Channel Four (Great Britain). (London Weidenfeld and Nicolson in association with Channel Four Television Co. and Nimrod Productions, 1986)
First published as a companion book to a Channel Four television series presented by Jocasta Innes and now handsomely reissued, this bestselling book opens up a vast range of visual possibilities to the home decorator -- from painted marquetry floors to sky ceilings, crackle-glazed tables to vinegar-grained chairs, and harlequin walls to wood-grained doors.

Author of the classic bestseller Paint Magic, Jocasta Innes is a leading innovator in this field, combining practical advice with flair and inspiration. This guide to painted finishes shows how walls, floors, ceilings, woodwork, fireplaces and furniture can all be transformed by simple do-it-yourself techniques in a multiplicity of imaginative and inexpensive ways. Each chapter covers the decorating process from the preparation required to the equipment needed, from the paint recipes to be followed to the methods you should use.

Talented designers give tips on new techniques, providing further inspiration and guidance. Stylish rooms shots, many taken exclusively for paintability by top interiors photographers Fritz von der Schulenberg, show the effects, both simple and exotic, and their sources of inspiration, while explanatory and step-by-step drawings demonstrate how they can be achieved. This book will have all home decorating enthusiasts reaching for their paintbrushes.
Includes bibliographical references (pages 187) and index
Keywords: House painting -- Amateurs' manuals